Bakteri Endofit asal Tanaman Tembakau sebagai Agens Pengendali Meloidogyne spp. - isnainy dinul Mursyalatiyus; Abdul Munif; Abdjad Asih Nawangsih (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2018)
Endophytic Bacteria from Tobacco Plant as Biocontrol Agent of Meloidogyne spp.Soilborne disease on tobacco plants caused by fungal and bacterial infection in association with root-knot nematode (Meloidogyne spp.) may cause significant yield loss. Endophytic bacteria have been recognized as biological control agent for Meloidogyne spp. as well as plant promoting growth agent. Research was conducted to evaluate endophytic bacteria isolated from tobacco plants as biological control agent for Meloidogyne spp. infecting tobacco. A total of 215 isolates of endophytic bacteria were isolated from root of two tobacco varieties, Kemloko and Prancak 95. Biosafety screening showed that 80 isolates (37%) and 7 isolates (8%) gave negative reaction on hypersensitivity test and hemolysis test, respectively. Seven isolates i.e. TPT3.10, TPT2.1, TK3n8, TK2t21, TK2n8, TK3n1 and TK2t11 were able to promote plant growth and increase the mortality of juvenile Meloidogyne spp. Physiological characterization of endophytic bacteria showed that most of the isolates were able to produce protease enzyme, phosphate, nitrogen and HCN. The same isolates were also able to suppress the number of galls from 80.09% up to 93.82%. Two isolates, TPT3.10 and TK2n8, are considered having the best suppression on root gall formation.